Food selection of wintering common cranes (Grus grus) in holm oak (Quercus ilex) dehesas in south-west Spain in a rainy season - Avilés, Jesus M.; Sánchez, Juan M.; Parejo, Deseada (Journal of Zoology, 2006)
In the holm oak Quercus ilex dehesas of the Iberian Peninsula, several food types occur that can be selected by birds through the winter. In this framework, diet composition and diet selection of common cranes Grus grus was studied during a rainy wintering season. The winter diet of the common crane is mostly herbivorous in the holm oak dehesas of south-west Spain with < 10% of items being of animal origin. Leaves and stems of sown cereal, bulbs, acorns and cereal grain are the most common vegetable food types. The diversity of the overall winter diet was similar among juveniles and among adults with and without juveniles in attendance. However, there were differences in diet composition between juvenile birds and their parents. Furthermore, the diet composition of adult cranes with juveniles in attendance was different from that of adult cranes without juveniles in attendance. Foraging abilities of juvenile cranes did not vary signi®cantly through the winter, suggesting a low effect of experience on diet differences between age classes. Our results point toward the existence of diet differences among the three considered crane categories related with differential habitat selection by family groups. The monthly pattern of choice of each food type differed from those expected according to the monthly pattern of food availability in the study area. Cereal grain was the most preferred food type when it was available. When cereal seed germinated, cranes shifted to acorns and bulbs which were then more pro®table
Keywords: age differences; Common Crane; food selection; Grus grus; holm oak dehesas; Quercus ilex

Food selection of wintering common cranes (Grus grus) in holm oak (Quercus ilex) dehesas in south-west Spain in a rainy season - Avilés, Jesús M; Sánchez, Juan M; Parejo, Deseada (Journal of Zoology, 2006)
In the holm oak Quercus ilex dehesas of the Iberian Peninsula, several food types occur that can be selected by birds through the winter. In this framework, diet composition and diet selection of common cranes Grus grus was studied during a rainy wintering season. The winter diet of the common crane is mostly herbivorous in the holm oak dehesas of south-west Spain with < 10% of items being of animal origin. Leaves and stems of sown cereal, bulbs, acorns and cereal grain are the most common vegetable food types. The diversity of the overall winter diet was similar among juveniles and among adults with and without juveniles in attendance. However, there were differences in diet composition between juvenile birds and their parents. Furthermore, the diet composition of adult cranes with juveniles in attendance was different from that of adult cranes without juveniles in attendance. Foraging abilities of juvenile cranes did not vary signi®cantly through the winter, suggesting a low effect of experience on diet differences between age classes. Our results point toward the existence of diet differences among the three considered crane categories related with differential habitat selection by family groups. The monthly pattern of choice of each food type differed from those expected according to the monthly pattern of food availability in the study area. Cereal grain was the most preferred food type when it was available. When cereal seed germinated, cranes shifted to acorns and bulbs which were then more pro®table
Keywords: age differences; Common Crane; food selection; Grus grus; holm oak dehesas; Quercus ilex

Common cranes Grus grus and habitat management in holm oak dehesas of Spain - Aviles, J M (BIODIVERSITY AND CONSERVATION, 2004)
Changes in agricultural policies have favored tree clearing and removal of shrubs to favor intensive farming in the holm oak Quercus ilex dehesas of Iberia. The effect of these changes for bird species wintering in this agricultural landscape has been rarely analyzed. Here the effects are studied of farming changes in traditional holm oak dehesas on population size, social structure and time budget of common cranes Grus grus in eight traditional wintering sites in Spain. The role of acorn availability, the principal winter food of the species, in relation to management is also assessed. The number of cranes in each wintering area was not related to degree of agricultural intensification, nor to the availability of acorns. However, crane flock size decreased, and the relative occurrence of isolated family groups increased in less intensively transformed wintering areas characterized by the predominance of fallow lands. The age composition of crane flocks varied with acorn availability since more juveniles were reported in areas with relatively lower acorn availability. Time budget was also related to acorn availability, since cranes spent relatively more time preening in those wintering areas with higher availability of acorns. Globally evidence suggests the need to maintain the fallow land (posios) to sustain the wintering populations of cranes in Iberia, since this agro-grazing system maintains most of the juvenile cranes using the western migratory route.
Keywords: acorns; agricultural policies; holm oak dehesas

Common cranes Grus grus and habitat management in holm oak dehesas of Spain - Aviles, J. M. (BIODIVERSITY AND CONSERVATION, 2004)
Changes in agricultural policies have favored tree clearing and removal of shrubs to favor intensive farming in the holm oak Quercus ilex dehesas of Iberia. The effect of these changes for bird species wintering in this agricultural landscape has been rarely analyzed. Here the effects are studied of farming changes in traditional holm oak dehesas on population size, social structure and time budget of common cranes Grus grus in eight traditional wintering sites in Spain. The role of acorn availability, the principal winter food of the species, in relation to management is also assessed. The number of cranes in each wintering area was not related to degree of agricultural intensification, nor to the availability of acorns. However, crane flock size decreased, and the relative occurrence of isolated family groups increased in less intensively transformed wintering areas characterized by the predominance of fallow lands. The age composition of crane flocks varied with acorn availability since more juveniles were reported in areas with relatively lower acorn availability. Time budget was also related to acorn availability, since cranes spent relatively more time preening in those wintering areas with higher availability of acorns. Globally evidence suggests the need to maintain the fallow land (posios) to sustain the wintering populations of cranes in Iberia, since this agro-grazing system maintains most of the juvenile cranes using the western migratory route.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: KLUWER ACADEMIC PUBL
Keywords: acorns; agricultural policies; holm oak dehesas

Does temporal variability of winter Common Cranes in the dehesas depend on farming practices? - Aviles, J. M.; Medina, F. J.; Sánchez, J. M.; Parejo, D. (Waterbirds, 2002)
The inclusion of Spain and Portugal within the European Community has brought about a change in the traditional farming practices in the dehesas of Iberia to intensive cereal and to irrigated crops. Here we use seven-year counts of Common Cranes in 38 wintering sites to evaluate whether habitat structure modified by farm- ing practices in the Holm Oak (Quercus ilex) dehesas is an important determinant of variability in winter crane num- bers. We extracted, from a set of nine variables that express different levels of human management in the Holm Oak dehesas, two factors that accounted for the 66% of the variance. The first factor was related to livestock utiliza- tion of the dehesas, while the second one reflected Holm Oak presence. We ran a general linear model to analyze the influence of farming practices (PC1 and PC2), landscape heterogeneity and roost site stability on inter- and in- tra-season variability in numbers of winter cranes. Livestock presence, Holm Oak presence, landscape heterogeneity and roost type stability did not explain intra- and inter- season variability in crane numbers wintering in the Holm Oak dehesas of Spain.
Keywords: Agricultural intensification; Common Crane; Grus grus; holm oak dehesas; southwestern Spain; winter stability

Does temporal variability of winter Common Cranes in the dehesas depend on farming practices? - Aviles, J M; Medina, F J; Sánchez, J M; Parejo, D (Waterbirds, 2002)
The inclusion of Spain and Portugal within the European Community has brought about a change in the traditional farming practices in the dehesas of Iberia to intensive cereal and to irrigated crops. Here we use seven-year counts of Common Cranes in 38 wintering sites to evaluate whether habitat structure modified by farm- ing practices in the Holm Oak (Quercus ilex) dehesas is an important determinant of variability in winter crane num- bers. We extracted, from a set of nine variables that express different levels of human management in the Holm Oak dehesas, two factors that accounted for the 66% of the variance. The first factor was related to livestock utiliza- tion of the dehesas, while the second one reflected Holm Oak presence. We ran a general linear model to analyze the influence of farming practices (PC1 and PC2), landscape heterogeneity and roost site stability on inter- and in- tra-season variability in numbers of winter cranes. Livestock presence, Holm Oak presence, landscape heterogeneity and roost type stability did not explain intra- and inter- season variability in crane numbers wintering in the Holm Oak dehesas of Spain.
Keywords: Agricultural intensification; Common Crane; Grus grus; holm oak dehesas; southwestern Spain; winter stability